Assessing Trade Credit Risk of Small and Micro Enterprises - Kiulkytė, Ligita (Jaunųjų mokslininkų darbai, 2017)
With a growing competition in the business environment, companies are forced to create favourable payment terms for customers. Trade credit today is a very popular payment method, which allows the buyer to delay payment and the seller to encourage sales. However, trade credit can cause problems to its provider when accounts remain unpaid for a long time or at all. Credit risk has to be monitored and assessed. There are a lot of measures and methods for managing credit risk, which help determine customer credit risk. However, each situation requires an amount of information that is usually obtained from financial statements. The structure of financial statements has been changed in Lithuania since 2016. It was noticed that an amount of information narrows the assessment of small and micro enterprises therefore it is important to evaluate whether that amount of information would affect the assessment of small and micro enterprises.Analysis of other authors’ research show that, using the new form of financial statements in Lithuania, some indicators cannot be calculated while assessing small and micro enterprises. 4 out of 15 most commonly used indicators have to be excluded from evaluations because of a lack of information in the new financial statements. Having analysed models proposed by other authors it was found that logistic regression is the most commonly used model for assessing small, micro and medium enterprises.
Keywords: Trade Credit; Credit Risk; Small and Micro Enterprises; Risk Assessment